Outcome of the Respiratory Syncytial Virus related acute lower respiratory tract infection among hospitalized newborns: a prospective multicenter study. (2nd July 2016) - Alan, Serdar; Erdeve, Omer; Cakir, Ufuk; Akduman, Hasan; Zenciroglu, Aysegul; Akcakus, Mustafa; Tunc, Turan; Gokmen, Zeynel; Ates, Can; Atasay, Begum; Arsan, Saadet; ,
Abstract: Aim : To determine the incidence and outcomes of respiratory syncytial virus (RSV)-related acute lower respiratory tract infection (ALRI) including morbidity, nosocomial infection and mortality among newborn infants who were admitted to the neonatal intensive care units (NICUs). Methods : A multicenter, prospective study was conducted in newborns who were hospitalized with community acquired or nosocomial RSV infection in 44 NICUs throughout Turkey. Newborns with ALRI were screened for RSV infection by Respi-Strip®-test. Main outcome measures were the incidence of RSV-associated admissions in the NICUs and morbidity, mortality and epidemics results related to these admissions. Findings: The incidence of RSV infection was 1.24% ( n : 250) and RSV infection constituted 19.6% of all ALRI hospitalizations, 226 newborns (90.4%) had community-acquired whereas 24 (9.6%) patients had nosocomial RSV infection in the NICUs. Of the 250 newborns, 171 (68.4%) were full-term infants, 183 (73.2%) had a BW >2500 g. RSV-related mortality rate was 1.2%. Four NICUs reported seven outbreaks on different months, which could be eliminated by palivizumab prophylaxis in one NICU. Conclusion : RSV-associated ALRI both in preterm and term infants accounts an important percent of hospitalizations in the season, and may threat other high-risk patients in the NICU.